The Empirical Study of College Students’ E-Learning Effectiveness and Its Antecedents Toward the COVID-19 Epidemic Environment - Wang, Cai-Yu; Zhang, Yuan-Yuan; Chen, Shih-Chih (Frontiers in Psychology, 2021)
Due to the impact of the COVID-19, universities and education departments are forced to suspend classes and depend on the usage of online teaching. To investigate the relationship among E-learning self-efficacy, monitoring, willpower, attitudes, motivations, strategies and the E-learning effectiveness of college students in the context of online education during the outbreak of COVID-19 , 519 first- to fifth-year undergraduate students at a medical university were selected in this study. Structural equation model (SEM) is used to analyze the data, and the results show that: (1) E-learning self-efficacy and monitoring have significant positive effects on E-learning strategies, and indirectly affect E-learning effectiveness through E-learning strategy; (2) E-learning willpower and attitudes have significant positive impacts on E-learning motivations, and indirectly affect E-learning effectiveness through E-learning motivations and strategies; (3) E-learning motivations significantly positively affect E-learning effectiveness, with E-learning strategies playing a mediating role; (4) There is a significant positive correlation between E-learning strategies and E-learning effectiveness; (5) The presence of E-learning experiences has a moderating effect on E-learning effectiveness and its influencing factors. It is recommended that instructors and students pay attention to these factors in the process of online sustainable education, so as to improve the E-learning effectiveness of college students.